PELESTARIAN BUDAYA BETAWI PERMAINAN ANAK CICI PUTRI DAN ULABANG/ WAK WAK GUNG : KAJIAN KANDUNGAN KECERDASAN JAMAK (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2010)
The focus of this paper is on Betawi’s children traditional games named Cici Puti and Wak-Wak Gung that are loaded with multiple intelligences content. The objective of this writing is to raise the importance of awareness of teachers in Jakarta, especially those who teach early learners, to promote traditional Betawi games with all of their advantages. The data collected is based on three previous study results: 1. Multiple intelligences in Betawi children games that uses songs, 2. Educational values in Betawi Folk songs, and 3. Betawi classical songs (Lagu Dalem); a study of existence, characteristics, and tips of studying them. The study found out that there are educational values in Betawi traditional games with songs. Based on the recent studies, teachers in Jakarta, especially the art teachers and early learners teachers, have not promoted Betawi folk songs optimally in learning process, especially the songs coming from traditional games. The main reason is that the art teachers do not fully master Betawi art especially the folk songs and songs coming from the traditional games. The games of Cici Putri and Ulabang/Wak-Wak Gung are the decendent of the traditional game of Betawi until recently is still played by the children in some communities of Betawi. Kata kunci: pelestarian, budaya Betawi, permainan anak Cici Putri, permainan anak Ulabang/Wah-Wak Gung